2022
DOI: 10.4314/ahs.v22i3.71
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the level of disaster preparedness of Tunisian University Hospitals using the Hospital Safety Index: a nationwide cross-sectional study

Abstract: Background: Mid-way through the ‘Sendai Framework for Disaster Risk Reduction 2015-2030’, many nations are spending time, money and effort to enhance their level of preparedness facing disasters, on the other hand communities, countries and even continents are being left behind. Objectives: This study was conducted aiming at evaluating the level of disaster preparedness and response of Tunisian University Hospitals. Methods: This is a cross-sectional nationwide study conducted in Tunisia, from Nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…It was done in the study of Lamine H et al (2022). The evaluation of the level of preparedness and response, including nine hospitals of the University of Tunis in disasters, showed that 7 of the nine university hospitals had safety category “B” in communication systems with overall safety indicators between 37% and 62% [ 59 ]. The study by Zaboli R et al (2014) conducted a study on communication and information systems related to emergency management, which stated that the personal information of personnel is the most important and critical element for any system, especially crisis management.…”
Section: Discussionmentioning
confidence: 99%
“…It was done in the study of Lamine H et al (2022). The evaluation of the level of preparedness and response, including nine hospitals of the University of Tunis in disasters, showed that 7 of the nine university hospitals had safety category “B” in communication systems with overall safety indicators between 37% and 62% [ 59 ]. The study by Zaboli R et al (2014) conducted a study on communication and information systems related to emergency management, which stated that the personal information of personnel is the most important and critical element for any system, especially crisis management.…”
Section: Discussionmentioning
confidence: 99%
“…Disasters of different types can disrupt hospital operations and represent considerable obstacles to patient care. Hospitals often have emergency management processes to deal with these various types of disasters and maintain the safety and well-being of clients, employees, and the community [ 13 ].…”
Section: Reviewmentioning
confidence: 99%
“…Although it is estimated that the HSI has been used to assess the safety of more than 3500 facilities worldwide [ 6 ], scientific publications on it are scant. Most of the studies found in the literature refer to a few countries, and they are either reporting the results of HSI assessments [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ], comparing preparedness across cities [ 17 ], or adapting the tool to specific contexts [ 18 , 19 , 20 ]. There is a lack of studies on the methodological implications of using the HSI as a primary data collection tool and a shortage of qualitative studies.…”
Section: Introductionmentioning
confidence: 99%